PENERAPAN PENDIDIKAN PERDAMAIAN DALAM TRIPUSAT PENDIDIKAN PERSPEKTIF HADIS NABI - Bening Anjaswara; Sofyan Sauri (Tarbiyatuna Kajian Pendidikan Islam, 2024)
Indonesian society is a heterogeneous society consisting of various tribes, cultures, beliefs, and groups. With this diversity, it is very possible for conflicts to occur in society. Efforts to avoid conflict and create a peaceful life in the community are by implementing peace education. This article aims to discuss how peace education can be applied to the three education centers using the perspective of the Prophet's hadith. In this case, researchers try to see how the figure of the Prophet Muhammad exemplifies and teaches peace education to his people in the family, school, and community. This research uses a literature study study with a content analysis model. Where researchers will analyze the hadiths of the Prophet that have messages of peace which will then be seen how the role of these hadiths in the application of peace education in the three education centers. The results of this study show that the hadith of the Prophet is proven to contain the teachings of peace in the family, school, and community environment which can be used as a guideline in the application of peace education in the trhee education centers.